A Conceptual Framework for SME Growth in China Based on‎Strategic Resources, Capabilities, and Sustainability - Yongming, Chen; Latip, Malisah; Sharkawi, Ismawati; Jusoh, Nurul Hidayu Mat (International Journal of Accounting and Economics Studies, 2025)
The sustainable growth of Small and Medium-sized Enterprises (SMEs) is central to economic resilience and inclusive development. In ‎China, government-led initiatives have spurred the expansion of business incubation institutions to support entrepreneurship and innovation. ‎However, existing studies have not sufficiently examined how resource-based mechanisms within incubation models affect SME development. This conceptual paper proposes an integrated framework grounded in the Resource-Based View (RBV), Dynamic Capabilities Theory, and the Natural Resource-Based View (NRBV) to explore the relationship between incubation services, resource orchestration, and ‎SME performance. The study identifies key internal and external resources, such as financial, human, technical, and sustainability-oriented ‎capabilities, that influence incubator effectiveness. It highlights the importance of strategic resource alignment, capability development, and ‎environmental adaptation in supporting SME competitiveness. The framework also considers contextual factors such as regional disparities ‎and sector-specific needs, which may moderate the effectiveness of incubation efforts. By situating the discussion within China’s evolving ‎innovation ecosystem, particularly in regions like Fujian Province, the study contributes to theory-building in incubation research and ‎informs the design of more effective and context-responsive incubation strategies. The framework serves as a foundation for future empirical ‎research aimed at enhancing the long-term impact of incubation models on SME innovation, sustainability practices, and strategic growth‎.
Keywords: SMEs; Innovation Incubation; Resource-Based View; Incubation Model; Sustainable Development; China; VRIN Framework